Gas-solid Two-phase Flow of Pulverized Coal by ECT: A Review - Nur Arina Hazwani Samsun Zaini; Ruzairi Abdul Rahim; Herman Wahid; Mimi Faisyalini Ramli; Nasarudin Ahmad; Mohamad Shukri Manaf; Yusri Md. Yunos; Anita Ahmad; Ahmad Azahari Hamzah; Chan Kok San; Farah Aina Jamal Mohamad; Navintiran; et al. (MyCT Publishers, 2024)
Non-Indexed Publication